Campus Canopy, 1937-01-15 - The Campus Canopy, The Georgia State Woman's College (Georgia State Womans College, 1937)
Elizabeth Wysor Versatile Contralto is Second Artist -- Working on Swimming Pool Project to Begin Immediately -- Panel Discussion Given For AAUW -- Dean Dorman to Address the Student Government -- Secretary of Foreign Missions Challenges -- Girls in Chapel Talk -- Perfect Radio Voice of Mrs. Petch brings Norway to Students --
Georgia State Womans College Student Newspaper
Keywords: Valdosta State University -- Periodicals